Saudi Arabia and the US since 1962 : allies in conflict - Bin Hethlain, Naif (SAQI, 2010)
Since the 1960s Saudi Arabia and the US have maintained a strategic alliance which has often involved a delicate diplomatic balancing act. Characterized by overlapping interests and mutual dependency - the US on the Kingdom for its oil and regional influence, Saudi Arabia on the US for security and legitimacy - Saudi-US relations have withstood successive changes of kings and presidents alike. However, since 9/11 officials in both countries have been reluctant to proclaim their relations openly for fear of national opposition. Arguing that Saudi-US relations are critical to developments in the Middle East, Naif bin Hethlain revisits critical past events - Egypt's involvement in Yemen, the Israel-Palestine conflict, the Gulf Wars, and the fall of the Twin Towers, among others - and uses them as a framework with which to examine the two nations' complex relationship. Insightful and exhaustively researched, "Saudi Arabia and the US since 1962" is a nuanced assessment of over forty-five years of geopolitics.